Effect of ischemic preconditioning on repeated sprint ability in team sport athletes - Gibson, N.; Mahony, B.; Tracey, C.; Fawkner, S.; Murray, A. (Journal of Sports Sciences, 2015)
This study investigated whether ischemic preconditioning (IPC) in a trained population affected repeated sprint performance. A secondary aim was to assess responses according to gender. Sixteen (nine females and seven males) well trained team sport athletes took part in a randomised crossover study design. Participants underwent an IPC and placebo treatment involving three periods of 5 min occlusion applied unilaterally (3 × 5 min occlusion to each leg) at either 220 mmHg or 50 mmHg. Each period of occlusion was followed by 5 min reperfusion. Following treatment 5 × 6 s maximal effort sprints were undertaken on a cycle ergometer against 7.5% body mass, each interspersed by 24 s recovery. Measured parameters included peak power, total power, percentage decrement, post-exercise blood lactate and ratings of perceived exertion. Nor within subject main effect for IPC was observed, neither was there an interaction effect with gender. Effect sizes were trivial (ES < 0.2) with the exception of a moderate (ES < 1.2) change in post-exercise blood lactate in the female cohort (1.6 ± 0.4 mmol-1 lower following IPC). Results suggest no benefit to team sport players in utilising IPC as a means of enhancing repeated sprint performance. A lower blood lactate response in female participants following IPC may suggest improved blood flow through vasodilation.